Association of -1082 interleukin-10 gene polymorphism in Peruvian adults with chronic periodontitis - Chambrone, Leandro (Med Oral Patol Oral Cir Bucal, 2014)
Objectives: The aim of this study was to assess association of the -1082 IL-10 gene polymorphism with chronic periodontitis CP in a Peruvian population. Study Design: Samples of venous blood and DNA were obtained from 106 Peruvian subjects: a) 53 periodontally healthy; and b) 53 with CP. The association of the -1082 IL-10 promoter sequences was assessed by Polymerase chain reaction-restriction fragment length polymorfism (PCR-RFLP). Student’s t test were used to assess the clinical parameters, as well as the χ2 test and the odds ratio (OR), with 95% confidence intervals (CI) used performed for estimates regarding genotype and allele frequencies. Results: There were statistically significant differences between groups regarding the mean bleeding on probing, mean attachment level and mean probing depth (p < 0.00001) indicating that the matching based on the evaluated groups was adequate. The χ2 test found a statistically significant imbalance of genotypes between groups (p = 0.0172). The prevalence of CP was significantly higher in subjects harboring at least one A allele at position -1082 (AA and GA genotypes) in comparison to patients with the GG genotype (OR = 2.96; CI: 0.52; 5.41; p = 0.0099). Equally, subjects with the AA genotype were significantly associated to a diagnosis of CP (OR = 2.71; CI: 0.38; 5.04; p = 0.0231). On the other hand, subjects presenting a healthy periodontal status presented at least one G allele in comparison with the AA genotype (OR = 0.37; CI: 0.05, 0.69; p = 0.0231). For subjects with the GG genotype, the same positive association was observed (OR = 0.34; CI: 0.06, 0.62; p = 0.0099). There were no significant differences between groups amongst subjects with the GA genotype (OR = 1.19; CI: 0.22, 2.16; p = 0.6774). Conclusions: Within the limits of this study, IL-10 gene polymorphism at position -1082 does not appear to be associated to CP. Conversely, subjects with AA genotype seem to be at an increased risk of developing CP. Key words:According to MeSH documentation, chronic periodontitis, cytokines, genetic polymorphism, interleukin-10, periodontal disease.